COMMUNITY DYNAMICS AND THE LIFE CYCLE OF PEOPLE AT RISK OF NATURAL DISASTERS (2024)
This research aims to analyze the relationship between attachment to place, identity to place, and sense of community with age, represented by ranks, of people living in neighborhoods at risk of natural disasters in the city of Ibagué, Colombia. This is a quantitative study with a correlational-exploratory scope, with the participation of 862 subjects from the 13 communes of the city of Ibagué, aged between 10 and 89 years. The results suggest that there is a positive relationship between the variables of attachment to place, identity to place, and sense of community with the age of its inhabitants. In addition, it was possible to establish that people between 40 and 59 years of age present better levels of attachment to place, identity to place and sense of community than people in the other age ranges. © (2024), (Associacao Brasileira de Psicologia Social).